E-Voting and identity : 5th International Conference, VoteID 2015, Bern, Switzerland, September 2-4, 2015, Proceedings /: 5th International Conference, VoteID 2015, Bern, Switzerland, September 2-4, 2015, Proceedings. (2015) - Unknown
No abstract available